2017
DOI: 10.1002/ejhf.874
|View full text |Cite
|
Sign up to set email alerts
|

Reduced regional cerebral blood flow in patients with heart failure

Abstract: Aim Heart failure (HF) patients show significant lateralized neural injury, accompanied by autonomic, mood, and cognitive deficits. Both gray and white matter damage appears, and likely develops from altered cerebral blood flow (CBF), a consequence of impaired cardiac output. However, the distribution of regional CBF changes in HF patients is unknown, but is an issue in determining mechanisms of neural injury. Our aim was to examine regional CBF changes in HF over control subjects using non-invasive pseudo-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 64 publications
3
70
0
2
Order By: Relevance
“…Also, this study utilized a 3.0‐Tesla compared to a 1.5‐Tesla MRI machine, which produces higher‐resolution images with greater anatomic details. Lateralization of brain tissue abnormalities was noteworthy, however lateralized brain injury in autonomic, anxiety, depression, and cognition regulatory sites are often observed in other conditions (Kumar et al, ; Roy et al, ; Tummala et al, ). The aberrations here might result from low cardiac output, endothelial dysfunction, ischemic changes, and underlying perfusion deficits in the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this study utilized a 3.0‐Tesla compared to a 1.5‐Tesla MRI machine, which produces higher‐resolution images with greater anatomic details. Lateralization of brain tissue abnormalities was noteworthy, however lateralized brain injury in autonomic, anxiety, depression, and cognition regulatory sites are often observed in other conditions (Kumar et al, ; Roy et al, ; Tummala et al, ). The aberrations here might result from low cardiac output, endothelial dysfunction, ischemic changes, and underlying perfusion deficits in the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Regional vascular recruitment is modulated by functional activity and local oxygen demands and is locally controlled by a range of factors addressed as ‘neuro‐vascular unit’, a heterogeneous structure composed of different cell types including astrocytes, pericytes, endothelial cells of the blood brain barrier, microglia, and neurons . Regional hypoperfusion has been observed in HF in multiple brain areas being largely lateralized towards the right side in the occipital, temporal, frontal, and parietal regions . Bilateral areas of reduced blood flow were observed in the prefrontal cortex, frontal white matter, anterior corpus callosum, thalamus, hippocampus, amygdala, and occipital cortex.…”
Section: A Impaired Cerebral Perfusionmentioning
confidence: 99%
“…The decreased regional perfusion may contribute to the autonomic, mood and cognitive regulatory deficits observed in HF. Further, impaired perfusion of multiple brain areas involved in control of vision, language and speech has been observed that could explain the respective deficits in HF patients …”
Section: A Impaired Cerebral Perfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…A position paper from the Heart Failure Association (HFA) reviews the heart and brain interactions in patients with heart failure (HF) . These include cerebral hypoperfusion, causing either ischaemic stroke, symptomatic or not, or a progressive decline in brain function, abnormalities in cortical functions, with cognitive decline, dementia, depression and anxiety, abnormalities in the autonomic nervous system and cardiac reflexes, changes related to HF treatment. A final section of this fascinating review covers the existing gaps in knowledge and unresolved issues …”
Section: Heart and Brainmentioning
confidence: 99%